Photocurrent Spectroscopy Applied to Semiconductor Thin Films: CDS - Azuero, Pedro (2001)
In this work, we present results of spectral photocurrent measurements in the quantitative diagnostic of semiconductors, in the specific case of cadmium sulfide (CdS) thin films. We present three measurement modalities. The results are each other complementary and confirms, thatthe most relevant energy levels in CdS, from the photoelectric point of view, correspond to the values: 2,0; 2,26; 2,38; 2,47 and 2,60 eV